A water quality investigation around an oil refinery in Hungary using the Fontinalis antipiretica (HEDW.) as bioindicator - Rabnecz, Gyula (Acta Biologica Szegediensis, 2008)
In this study the aquatic moss Fontinalis antipyretica (Hedw.) was used to indicate the relative levels of water pollution by ten heavy metals: Cd, Cr, Cu, Ni, Pb, V, Zn, Al, Fe and Pb at the territory of an oil refinery at the river Danube in Hungary. For the sake of complex comparison of environmental loads, CO2-gas exchange and chlorophyll-fluorescence parameter Fv/Fm were measured as complementarity to elemental analysis. A 36 days long period was studied in the summer of 2007. The water biomonitoring did not indicate the significant increasing of elemental load by the oil-refinery.